(untitled) (Journal of actual problems of jurisprudence, 2020)
The indicator of the correct development of society determines the life expectancy and gross domestic product per capita of members of society. With a high amount of domestic product, this indicator is not a developer. Therefore, the definition of quality of life is systematically determined by several parameters. If we focus on Kazakhstan joining the thirty developed countries, then we must turn to the ideas of leading states. On this path, the experience of OECD member countries is of great importance for Kazakhstan. The quality of life of a person who has reached retirement age, if you decide the quality of life of a person through employment, is one of the topical issues for the state. This question is not only for Kazakhstan, but also in the world has not lost relevance. Life-span steadily increases in the whole world that is blessing for people, but can be problematic for society and state. If nothing will be done for the change of existent charts of work and retiring, number of elderly nonactive people that will have to render support on every worker, can grow approximately on 40% in a period between 2018 and 2050 for years on the average in a region OECD.It will brake the height of standard of living, and also to render enormous pressure on the young generation, that will finance the systems of social defence.The improvement of prospects of employment of elderly workers will have a decision value.What do recommendations consist in OECD? How can the states give the best working stimuli and possibilities to the elderly people? To this article generalization of basic problems and recommendations is driven on questions of the politics sent to the assistance to employment in senior age.Certain suggestions are done on perfection of social legislation with the purpose of strengthening of guarantees of the pension system and increase of level of social defence, taking into account recommendations OECD. Key words: pension, public welfare, retirement age, OECD.